An observational study to assess feto-maternal outcome in severely ill COVID-19 positive pregnant females admitted at dedicated COVID care center of southern Rajasthan - Meena, Pooja; Verma, Savitri; Jourwal, Aayush; Gandhi, Sudha; Tvinwal, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: COVID-19 infection is caused by corona virus SARS-COV2. the aim of the study is to assess feto-maternal outcome in severely ill covid positive pregnant females. Methods: An observational study was conducted at dedicated covid care center, RNT medical college Udaipur from Jan 2021 to May 2021 among pregnant females. In this study out of 236 total covid positive pregnant patients, 54 patients which could not maintain oxygen saturation, according to NIH criteria were included in our study. Results: Out of 54 pregnant women, 24 women delivered with 2 twin pregnancies. Out of this 67% underwent cesarean section and 33% were delivered by vaginal route. Postpartum hemorrhage seen in 29% of patients. Maternal death reported in 39% of patients. Out of 54 patients 38 patients were admitted in ICU. Invasive ventilation received by 26% of patients while oxygen received by non-invasive ventilation (15%), Bains (18%) rest by NRBM and venturi mask (41%). Remdesivir were given in 26 (48%) patients. Conclusions: Our study suggests there may be increased risk of adverse pregnancy outcome for mother and fetus. COVID-19 in pregnancy was associated with risks of pre-eclampsia, stillbirth, preterm birth, PPH. Similar to general population comorbidities do play a role in the outcome of disease in pregnancy. Further studies are needed for effective strategies to prevent adverse outcomes in pregnant females with COVID-19.